Agro biological methods of obtaining early and high-grade cotton harvesting - Mahammadjonov Zuhriddin Mukhiddin o’g’li; O.O.Ibragimov (Zien Journals, 2022)
this article provides information on the methods of obtaining a high yield from cotton, varieties and seeds of cotton, how to obtain a crop
Keywords: cotton cultivation; moisture; soil; cotton